GENOTIPADO MEDIANTE MICROSATÉLITES DE ADN Y SCAR EN Oreochromis niloticus “tilapia gris” y “tilapia roja” DEL CENTRO DE CRIANZA DE TILAPIA, UNIVERSIDAD NACIONAL DE TRUJILLO. - Arqueros Avalos, Monica Luz (2015)
In order to register genetic variations between two populations of Oreochromis niloticus, "red tilapia" and "grey tilapia", microsatellite primers UNH 115, 123, 106, 180, 995, 136 and 190, GM 180 and 271, endogenous gene β-actin and SCAR markers 5RY/5F and 5FX/5R were used in this study. PCR products for UNH 190, 180, 115, 123, 106, 995 and 136, and GM 180 ranged from 143 to 178bp. On the other hand, the GM 271, β-actin, and SCAR 5RY/5F and 5FX/5R markers were larger with 702, 723, 256 and 956bp. UNH 106 microsatellite amplified in "red tilapia" only, so the other markers are not informative to differentiate "gray tilapia" from "red tilapia". Regarding SCAR 5RY/5F and 5FX/5R markers association with the phenotypic sex, unequivocally, was recorded. Keywords: Microsatélites, SCAR marker, Oreochromis niloticus, tilapia.